2012
DOI: 10.1080/01419870.2011.634981
|View full text |Cite
|
Sign up to set email alerts
|

Roma women in Athenian firms: do they face wage bias?

Abstract: Standard-Nutzungsbedingungen:Die Dokumente auf EconStor dürfen zu eigenen wissenschaftlichen Zwecken und zum Privatgebrauch gespeichert und kopiert werden.Sie dürfen die Dokumente nicht für öffentliche oder kommerzielle Zwecke vervielfältigen, öffentlich ausstellen, öffentlich zugänglich machen, vertreiben oder anderweitig nutzen.Sofern die Verfasser die Dokumente unter Open-Content-Lizenzen (insbesondere CC-Lizenzen) zur Verfügung gestellt haben sollten, gelten abweichend von diesen Nutzungsbedingungen die in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
21
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 18 publications
(23 citation statements)
references
References 46 publications
2
21
0
Order By: Relevance
“…The larger part of the gap was attributable to differing returns to characteristics (for example, differing pay premiums for different university degrees), differences in social or ethnic capital, or other unobservable factors such as discrimination. The study also showed that sorting across occupations and sectors did not affect this result significantly [9]. The study based on the four Hungarian surveys between 1993 and 2007 confirms these results: Differences in characteristics can explain only about half of the wage gap between employed Roma and non-Roma populations (not accounting for differences in selection into employment) [7].…”
Section: World Of Laborsupporting
confidence: 72%
“…The larger part of the gap was attributable to differing returns to characteristics (for example, differing pay premiums for different university degrees), differences in social or ethnic capital, or other unobservable factors such as discrimination. The study also showed that sorting across occupations and sectors did not affect this result significantly [9]. The study based on the four Hungarian surveys between 1993 and 2007 confirms these results: Differences in characteristics can explain only about half of the wage gap between employed Roma and non-Roma populations (not accounting for differences in selection into employment) [7].…”
Section: World Of Laborsupporting
confidence: 72%
“…To do this we apply a modified Blinder-Oaxaca (Blinder 1973;Oaxaca 1973) framework. The Blinder-Oaxaca decomposition technique has been predominantly used in labour economics literature to study gaps in wages and employment, mostly across ethnic groups and gender (e.g., Drydakis 2012;Croucher et al 2018). Recently, this method has also been applied in the field of public health literature to explore differences in obesity across racial groups, gender, and regions in North America (e.g., Sen 2014).…”
Section: Decomposition Analysismentioning
confidence: 99%
“…Feminist economists fight for the abolition of male dominance against women, and women's right to freedom of opportunity, conditions and choice, which will affect their education, career and wages. A comparable analysis holds for racial and ethnic minorities (Drydakis, 2012;2017).…”
Section: Causes and Policy Implications Of Wage Discriminationmentioning
confidence: 99%
“…Fair employment laws raise the cost of discrimination and discourage employers from practising discrimination. In reality, studies suggest that wage discrimination is a timeless phenomenon (Weichselbaumer and Winter-Ebmer, 2005;Drydakis, 2012;Blau and Kahn, 2017;Drydakis et al, 2017).…”
Section: Causes and Policy Implications Of Wage Discriminationmentioning
confidence: 99%
See 1 more Smart Citation